EVALUATE THE EFFECTIVENESS OF OUTSOURCING YOUR BUSINESS - Kaharova Nilufar Erkinjonovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article is devoted to the problem of assessing the cost-effectiveness of business processes of enterprises and organizations, which are considered as economic systems from the point of view of technological approaches.